What about the family? The role and meaning of family in the integration of migrant children: Evidence from Slovenian schools - Medarić, Zorana; Gornik, Barbara; Sedmak, Mateja (Frontiers in Education, 2022)
Based on field research in Slovenian schools, the article examines the role of the family in the integration process of migrant children. While migrant children perceive the family as the most important factor influencing their overall well-being and life satisfaction, research shows that parents of migrant children are often not involved in school activities and life. The article explores how the role of parents in the integration process of migrant children in the school environment is understood at the policy level and how it is perceived by migrant children and the educational community. It also explores what are the main barriers to the involvement of migrant parents in schools and what are the existing practices and experiences in Slovenian schools. The analysis is based on qualitative research in Slovenian schools with children and the educational community conducted as part of the Migrant Children and Communities in a Transforming Europe (MiCREATE) project.